SIGNIFIKANSI PENGAJARAN BAHASA INGGRIS DALAM PROSES PENGEMBANGAN ISLAMIC STUDIES - *, Riskiana; *, Marlina; Azzuhri, Muhandis; Ula, Miftahul (IAIN Pekalongan, 2009)
The teaching of English language has significant and strategic contribution. English language as a tool is used to understand and study many literatures of Islamic Studies use English language. This is as cause of the developing of Islamic Studies that is taken in hand by West. They have published their thought in Islamic Studies using English language as an international language in many academic publishing. Besides that, the developing of Islamic Studies is not discharged with the other science, including language. In line with this statement, STAIN Pekalongan has taken a new policy relating to the English language teaching. The goal of that policy is to maximize the process of English language teaching, so the students’ ability in English is better than before and could be utilized in developing of Islamic Studies. Based on that reason, this research explored four problems. First; students’ perception on English language teaching in STAIN Pekalongan. Second; significance of English language teaching for students’ Islamic Studies developing. Third; relationship between perception on English language teaching and the developing of Islamic Studies. Fourth; competency in English language teaching expected by the students.